Duplexsonography of the mesenteric vessels – a critical evaluation of inter observer variability - Ignee, A.; Boerner, N.; Bruening, A.; Dirks, K.; von Herbay, A.; Jenssen, C.; Kubale, R.; Sattler, H.; Schuler, A.; Weiss, H.; Schuessler, G.; Dietrich, C. F. (Zeitschrift für Gastroenterologie, 2016)
Introduction: The number of publications concerning mesenteric Doppler sonography (mesDS) is immense and does not correlate with the frequency of its use in clinical practice. This is astonishing since it provides real time blood flow (perfusion) information without side effects. Despite uncontrollable parameters like the technical limitations in some situations the optimization of (possibly) controllable parameters like standardization, production of normal values and reduction of the investigator variability by evaluating stable parameters could change the situation.Patients and methods: 10 investigators experienced in abdominal sonography (“DEGUM-Seminarleiter”) performed mesenteric Doppler sonography in 5 healthy subjects with 5 different machines.Results: The portal vein at the confluence and the common hepatic artery provide a significant portion of investigations with intromission angles of more than 60°. Values of diameter, resistance index and pulsatility index of the celiac trunc could be obtained with inter-observer variability values below 25 %. The proper and the common hepatic artery show no differences in inter-observer variability values, whereas the intrahepatic measure point of the portal vein showed a higher reproducibility.Discussion: We define frame conditions for future mesenteric Doppler studies: the portal vein should be investigated at the intrahepatic measure point. Pathophysiological studies should refrain from velocity parameters except in the case of larger vessels running in a straight course towards the probe.
Keywords: Darm; infektiöse Kolitis; ischämische Kolitis; Sprue; chronisch entzündliche Darmerkrankung; Leber